2016
DOI: 10.3233/cbm-160576
|View full text |Cite
|
Sign up to set email alerts
|

Novel mutations of PIK3CA gene in head and neck squamous cell carcinoma

Abstract: PIK3CA gene plays a crucial role in carcinogenesis in general and HNSCC in particular. The identification of five novel mutations suggest that Saudis may have different frequencies of somatic genetic alterations that may influence HNSCC compared to other populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Our study cohort is in line with this, as 66% of the patients were males and 58% of the male patient group were smokers compared with 18.75% in female patients. It is known that the higher-grade HNSCC tumors are associated with a higher number of mutations 17. This has also been confirmed by the present study, where a higher number of mutations were observed in high pathological grade tumors ( P =0.026).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study cohort is in line with this, as 66% of the patients were males and 58% of the male patient group were smokers compared with 18.75% in female patients. It is known that the higher-grade HNSCC tumors are associated with a higher number of mutations 17. This has also been confirmed by the present study, where a higher number of mutations were observed in high pathological grade tumors ( P =0.026).…”
Section: Discussionsupporting
confidence: 91%
“…Sparse data are available on EGFR-TK domain mutations in HNSCC globally and in the Saudi population. Previously, the PIK3CA mutation pattern in HNSCC patients of Saudi origin was studied, and a high frequency of PIK3CA mutations and five novel mutations were reported 17. The PI3K signaling molecules upon binding to the phosphorylated TK initiate a cascade of intracellular signal transduction pathways.…”
Section: Introductionmentioning
confidence: 99%
“…The thermocycling conditions were as follows: 1 cycle of 5 min at 95°C; 40 cycles of 30 sec at 95°C, 30 sec at 54°C, and 30 sec at 72°C; and 1 cycle of 5 min at 72°C. Subsequently, the PCR products were analyzed on a 2% agarose gel, which indicated the expected amplicon for exon 9 of 195 bp and for exon 20 of 338 bp (24). The sequence analysis was performed using the CodonCode aligner software (CodonCode Corporation, Centerville, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Distribution of polymorphisms and novel mutations on exon 2 and exon 5 of UCP1 gene was carried out using capillary sequencing by ABI 3500 genetic analyzer (Thermo Scientific, CA, USA) as previously reported [ 23 ]. The targeted gene sequence was amplified using polymerase chain reaction with specific primers for Exon 2 (Fwd-5’TCTGCACCTTTCTTATTTC3’ Rev-5’TCTCGCCAATTTGTTATGAA3’) and Exon 5 (Fwd-5’CAAAAGTCTGATGTTGAC3’ Rev-5’GAAATCTGTGGCAAGGAAAAGT3’) on a thermal cycler S1000 (Bio Rad, Hercules, California, USA).…”
Section: Methodsmentioning
confidence: 99%